Comparison of Efficacy between Acupuncture Therapies in Improving Sacroiliac Joint Malposition: A Systematic Review and Meta-Analysis. (11th January 2022) - Liu, Liguo; Pan, Litao; Tian, Minne; Chen, Xiuhua; Lu, Liming; Xu, Guofeng; Sun, Jian; Kui, Yu
Abstract : Aim . To provide available quantitative evidence of efficacy and safety of acupuncture treatments for improving sacroiliac joint malposition. Methods . Databases such as the China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (CQVIP), Wanfang Database (Wanfang), China Biology Medicine disc (CBMdisc), PubMed, Web of Science, EMBASE, and Cochrane Library were searched by computer to collect the reports on acupuncture treatment of sacroiliac joint malposition from the database creation to July 20, 2021. The selection of included studies, data extraction and coding, and bias risk assessment were conducted independently by two reviewers. RevMan5.4 software was used for meta-analysis, and the results were expressed as mean difference (MD) or standardized mean difference (SMD), with a confidence interval (CI) of 95%. Results . A total of 10 randomized controlled clinical trials (RCTs) with 1019 participants were included. Their overall quality of methodology was not high, and there may be publication bias. Meta-analysis showed that the total effective rate of the treatment group was higher than that of the control group (OR = 2.74, 95% CI 2.00 to 3.74, P < 0.00001 ). The treatment group was better than the control group in improving VAS score (WMD = − 1.56, 95% CI -2.18 to -0.94, P < 0.00001 ). The ODI score of the treatment group was lower than that of the control group (WMD = − 6.04, 95% CI -7.05 to -5.02, P < 0.00001 ). With the improvement of the JOA score, the difference of iliac transverse diameter of sacroiliac joint dislocation and the index of sacroiliac joint malposition in the treatment group were better than those in the control group (P < 0.05 ). There was no significant heterogeneity among the studies. Conclusion . Acupuncture may have therapeutic advantages in improving sacroiliac joint malposition. Acupuncture and acupotomy provide a safe way to improve the related clinical symptoms and functional disorders in activity of sacroiliac joint dislocation. However, due to the low quality of the included literature, this conclusion still needs to be further verified by more high-quality and large-sample RCTs.